Immune Dysfunction and Inflammageing in NAFLD - Naimimohasses, Sara (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2023)
With a global prevalence of 25-40%, non-alcoholic fatty liver disease (NAFLD) is fast becoming the commonest cause of liver disease in the developed world [1]. Defined as increased hepatic lipid accumulation, approximately 25% of individuals with NAFLD go on to develop progressive disease with non-alcoholic steatohepatitis (NASH) and fibrosis, leading to cirrhosis with increased risk of decompensated chronic liver disease and hepatocellular carcinoma[2, 3]. Immune dysregulation with chronic inflammation is central to the pathophysiology of NAFLD[4, 5]. The liver functions as a key immune organ, with a large population of resident leukocytes, including Mucosal associated invariant T (MAIT) cells[6]. It is likely that activation of resident immune cells in addition to preferential hepatic migration of circulating leukocytes are critical in promoting the inflammation which drives disease progression, however, the non-invasive identification of hepatic inflammation remains a diagnostic challenge in clinical practice[2, 7]. In this thesis, Chapter 2 details a descriptive analysis of circulating and intrahepatic immune cells with a focus on MAIT cells and assessed for correlates of histological severity. The results showed that circulating monocytes were significantly reduced and this reduction was predictive of NASH, although there were no significant immunophenotypic changes on flow cytometric analysis. Circulating MAIT cells, particularly CD8+ MAIT cells and CD8+ T lymphocytes were reduced in comparison to healthy controls with advancing histological inflammation and fibrosis. Interestingly, on review of the intrahepatic compartment, only CD8+ T lymphocytes were reduced in NASH and advanced fibrosis. Composite quantification of circulating monocytes, neutrophil-lymphocyte ratio, CD8+ T lymphocytes and circulating MAIT cells was found to strongly correlate with NASH and significant hepatic fibrosis, with a greater AUC for advanced fibrosis compared to current non-invasive scores used to estimate NAFLD fibrosis inclusive of: FIB-4, NAFLD score and VCTE measurements. In chapter 3, changes in circulating and intrahepatic MAIT cells in association with dietary and exercise-based weight loss interventions were analysed. A 12-week dietary intervention program resulted in clinically and statistically significant weight reduction, which correlated with reductions in expression of the activation marker CD69 on circulating MAITs. Within the liver, weight loss correlated with a reduction in hepatic steatosis but was not associated with changes in histological features of inflammation or fibrosis. Weight loss was also not associated with any changes in the number or activation marker expression of intrahepatic MAIT cells. In contrast, despite more modest reductions in weight, the exercise intervention led to significant improvements in histological inflammation (as defined by hepatocyte ballooning) and fibrosis. These histological improvements were associated with increased expression of the terminal activation marker CD95 and reduction in the percentage of intrahepatic MAIT cells, suggesting that exercise has unique immunomodulatory effects promoting accelerated apoptosis of MAIT cells. These results support a potential pathogenic role of MAITs, with intrahepatic depletion coinciding with fibrosis regression. Finally, Chapter 4 investigated clinical features of systemic inflammation and accelerated ageing inpatients with NAFLD by performing frailty measures in a cohort of patients across a spectrum of disease severity. The results confirmed a high prevalence of frailty and pre-frailty amongst individuals with non-cirrhotic NAFLD, most notably amongst female patients. The frailty measures: SRFI, FI-LAB and 30STS were significantly associated and positively correlated with fibrosis stage. In conclusion, NAFLD is a state of chronic systemic inflammation resulting from persistent immune cell activation. Alterations in circulating immune cells both correlate with and are predictive of liver disease severity, whilst changes in intrahepatic MAIT cell populations are associated with histological improvements post exercise intervention. This chronic inflammatory state is also a factor in the development of frailty, with high rates of frailty and pre-frailty seen even in individuals with early stage NAFLD. These findings identify immunological changes that can be used to improve the non-invasive staging of NAFLD severity, in addition to highlighting effective therapeutic strategies and potential novel targets that can be used to improve outcomes for patients with NAFLD.
APPROVED
Keywords: Fibrosis; Mucosal Associated Invariant T cells (MAIT); Frailty; Sarcopaenia; Inflammageing; Non-alcoholic fatty liver disease (NAFLD)